2006
DOI: 10.1152/ajpgi.00565.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cytochrome P-450 reductase-null mice show reduced transcriptional response to quercetin and reveal physiological homeostasis between jejunum and liver

Abstract: P-450reductase-null mice show reduced transcriptional response to quercetin and reveal physiological homeostasis between jejunum and liver. Am J Physiol Gastrointest Liver Physiol 290: G63-G72, 2006. First published February 2, 2006 doi:10.1152/ajpgi.00565.2005.-Using mice deficient in hepatic cytochrome P-450 oxidoreductase (POR), which disables the liver cytochrome P-450 system, we examined the metabolism and biological response of the anticarcinogenic flavonoid, quercetin. Profiling circulating metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…However, the decrease in plasma fatty acid levels is consistent with the fact that quercetin modulates fatty acid metabolism in rats. Effects of quercetin on metabolism of energetic substrates were also reported by Mutch et al [27]. Using affymetrix gene chips and cytochrome P450 reductase knockout mice, they showed that after a short, 4-h exposure to a 0.62% quercetin diet, amino acid metabolism, lipid metabolism and glutathione metabolism pathways were altered in liver and intestines.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the decrease in plasma fatty acid levels is consistent with the fact that quercetin modulates fatty acid metabolism in rats. Effects of quercetin on metabolism of energetic substrates were also reported by Mutch et al [27]. Using affymetrix gene chips and cytochrome P450 reductase knockout mice, they showed that after a short, 4-h exposure to a 0.62% quercetin diet, amino acid metabolism, lipid metabolism and glutathione metabolism pathways were altered in liver and intestines.…”
Section: Discussionsupporting
confidence: 58%
“…Using affymetrix gene chips and cytochrome P450 reductase knockout mice, they showed that after a short, 4-h exposure to a 0.62% quercetin diet, amino acid metabolism, lipid metabolism and glutathione metabolism pathways were altered in liver and intestines. Moreover, genetically eliminating the expression of the phase I enzyme did not alter quercetin metabolism itself, but altered the tissue-specific location of differentially regulated major metabolism pathways by quercetin [27]. Several other flavonoids have also been shown to interfere with the homeostasis of fat storage and fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically altering lipid metabolism at the whole body level via ablation or overexpression of selected genes can influence metabolism in two different ways, either by directly altering energy supply and storage, and/or by altering signalling pathways that affect gene expression and protein content in an endocrine and exocrine manner, as highlighted by others (review) [18,19]. Therefore, interpretation of such experiments may be complex, as ablation of a gene in one tissue can affect metabolism in other tissues [20][21][22][23]. Since ablation of Fatp1 seems to reorganise lipid metabolism in various tissues [16], it is unclear whether the protection against diet-induced insulin resistance is attributable to ablation of Fatp1 in muscle or to adaptive alterations in lipid metabolism in other tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous reports have dealt with the relationships between liver and intestine in mice with deficient hepatic POR expression (Mutch et al, 2006(Mutch et al, , 2007, but neither study reported comparisons of the constitutive expression or activity of intestinal drugmetabolizing CYPs between wild-type and hepatic POR-null mice. The microarray data in the more recent study (Mutch et al, 2007) did show a modest increase in Fxr expression in the ileum of the hepatic POR-null mice, relative to that in WT mice, a finding confirmed here by RNA polymerase chain reaction analysis in the LCN mice.…”
Section: Regulation Of Intestinal P450 Expression By Livermentioning
confidence: 99%